2022
DOI: 10.3390/metabo12121207
|View full text |Cite
|
Sign up to set email alerts
|

Guanosine Prevents Spatial Memory Impairment and Hippocampal Damage Following Amyloid-β1–42 Administration in Mice

Abstract: Alzheimer’s disease (AD) is a progressive neurodegenerative illness responsible for cognitive impairment and dementia. Accumulation of amyloid-beta (Aβ) peptides in neurons and synapses causes cell metabolism to unbalance, and the production of reactive oxygen species (ROS), leading to neuronal death and cognitive damage. Guanosine is an endogenous nucleoside recognized as a neuroprotective agent since it prevents glutamate-induced neurotoxicity by a mechanism not yet completely elucidated. In this study, we e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 52 publications
1
1
0
Order By: Relevance
“…In summary, through an in-depth and comprehensive analysis of the serum metabolomics of T-T2DM and L-T2DM patients, we found that DMs mainly included pipecolic acid, lauric acid, guanosine and kaempferol and were mainly involved in lysine degradation, fatty acid biosynthesis, purine metabolism and metabolic pathways. Machine learning further identi ed guanosine as the most characteristic cognition-related metabolic biomarker for DCD in high-altitude, which is consistent with another study showing that guanosine can prevent spatial memory dysfunction and hippocampal damage after amyloid-beta administration in mice [31]. In addition, this study provides rst-hand evidence in diabetic with cognitive function in high-altitude.…”
Section: Discussionsupporting
confidence: 86%
“…In summary, through an in-depth and comprehensive analysis of the serum metabolomics of T-T2DM and L-T2DM patients, we found that DMs mainly included pipecolic acid, lauric acid, guanosine and kaempferol and were mainly involved in lysine degradation, fatty acid biosynthesis, purine metabolism and metabolic pathways. Machine learning further identi ed guanosine as the most characteristic cognition-related metabolic biomarker for DCD in high-altitude, which is consistent with another study showing that guanosine can prevent spatial memory dysfunction and hippocampal damage after amyloid-beta administration in mice [31]. In addition, this study provides rst-hand evidence in diabetic with cognitive function in high-altitude.…”
Section: Discussionsupporting
confidence: 86%
“…Guanosine displays anticonvulsant effect (De Oliveira et al, 2004), protective effect against ischemic conditions (Dal‐Cim et al, 2019; Hansel et al, 2015), and antidepressant‐like effects (Bettio et al, 2016). Also, guanosine has protective effects in AD rodent models (Coelho et al, 2022; Lanznaster et al, 2017; Pettifer et al, 2004), and improved mitochondrial function and ameliorated motor and cognitive behavior in rodent PD models (Marques et al, 2019) among others (Lanznaster et al, 2016; Massari et al, 2021; Schmidt et al, 2007). In addition, a potential anti‐aging effect of guanosine has been shown in glial cells (Souza et al, 2016).…”
Section: Introductionmentioning
confidence: 99%